2015
DOI: 10.1002/cncr.29614
|View full text |Cite
|
Sign up to set email alerts
|

Changes in body mass index in long‐term childhood cancer survivors

Abstract: BACKGROUND Previous studies have reported changes in the body mass index (BMI) with time in childhood cancer survivors (CCSs) during follow‐up. The limitations of these studies include that they described only a subgroup of survivors or used questionnaires with self‐reported heights and weights. The goal of this study was to examine BMI in a large cohort of long‐term CCSs and relate this to the BMI at diagnosis, age, sex, tumor type, treatment, and endocrine defects. METHODS All patients treated for childhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 27 publications
(40 reference statements)
3
20
0
1
Order By: Relevance
“…We also found that leukemia survivors who are overweight at diagnosis have a substantially higher risk of being overweight later in life. This is in line with previous observations of survivors of leukemia (11,(17)(18)(19) and other childhood cancers (44) and the general population, in all of whom overweight tends to track strongly throughout life (45). As in our study, others have found that more than two-thirds of ALL survivors who were overweight at diagnosis remained overweight at the end of, or after, treatment (18,19).…”
Section: Potential Mechanisms and Risk Factors: Results In Relation Tsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found that leukemia survivors who are overweight at diagnosis have a substantially higher risk of being overweight later in life. This is in line with previous observations of survivors of leukemia (11,(17)(18)(19) and other childhood cancers (44) and the general population, in all of whom overweight tends to track strongly throughout life (45). As in our study, others have found that more than two-thirds of ALL survivors who were overweight at diagnosis remained overweight at the end of, or after, treatment (18,19).…”
Section: Potential Mechanisms and Risk Factors: Results In Relation Tsupporting
confidence: 93%
“…Overall, CCSs and leukemia survivors treated with ≥20 Gy CRT were more likely to be overweight, which suggests that ≥20 Gy CRT is a risk factor for obesity in all CCSs irrespective of the diagnosis. The positive association between CRT and obesity has also been seen in adult survivors of a variety of different childhood cancer types (22,44). Although CRT was not stratified by dose amount, survivors in these studies were diagnosed between 1970-1986 (22) and 1966-1996 (44), and the majority might have received high-dose CRT.…”
Section: Potential Mechanisms and Risk Factors: Results In Relation Tmentioning
confidence: 92%
“…Seventeen studies ( n = 2032 participants) reported prevalence of overweight and obesity among patients with various types of brain tumours ; The study characteristics and results are described in Table . The age at diagnosis ranged from at birth to 24.8 year old.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 17 studies, eight were retrospective cohort studies , while three were longitudinal cohort studies and the remaining six were cross‐sectional studies . Nine studies included a non‐cancer comparison group (by recruiting controls or comparing to national populations). However, only four studies reported sample sizes and were included in the meta‐analysis to calculate estimation for non‐cancer controls.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of obesity in cancer survivors have found similarly troubling trends, with one reporting that 13% of survivors were obese (body-mass index > 30), and that another 28% were overweight, with a body-mass index between 25 and 30 [121]. Among 893 childhood cancer survivors in The Netherlands, only girls had a significantly higher incidence of obesity [122]. Another study of more than 200 survivors from the Pediatric Long-Term Survivor Clinic at the University of Rochester found that their mean LDL-cholesterol concentration was higher than that of 70 healthy siblings [123].…”
Section: Statins In Primary Preventionmentioning
confidence: 99%